2006
DOI: 10.1111/j.1538-7836.2005.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein contributes to the hypercoagulable state in coronary artery disease

Abstract: Summary. Objectives: Elevated plasma C-reactive protein (CRP) levels predict coronary events, but it is unclear whether CRP plays a role in thrombosis associated with these events. We investigated tissue factor (TF) induction by CRP on peripheral blood mononuclear cells (PBMC) from patients with coronary disease. Patients and Methods: PBMC from 35 patients with stable angina (SA) in study 1, 10 male patients with SA, 10 with unstable angina (UA) and 10 matched controls in study 2, and 25 patients with inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Furthermore, CRP has been reported to promote monocyte chemotactic activity in response to MCP-1 via upregulation of monocyte CCR2 (35 ). By contrast, CRP had no effects in stimulating TF mRNA in highly purified monocytes from healthy patients (36 ) or angina patients (37 ), indicating that TF stimulation by CRP may be favored by the presence of other circulating cells and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, CRP has been reported to promote monocyte chemotactic activity in response to MCP-1 via upregulation of monocyte CCR2 (35 ). By contrast, CRP had no effects in stimulating TF mRNA in highly purified monocytes from healthy patients (36 ) or angina patients (37 ), indicating that TF stimulation by CRP may be favored by the presence of other circulating cells and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 76%
“…15 In addition, we previously showed that monocytes from patients with unstable angina are preactivated and express TF. 12 Here, we have shown that PBMCs and monocytes from patients with MetS are more responsive to LPS than cells from normal subjects, thus suggesting that cells from MetS patients have undergone pre-activation. Therefore, pre-activated monocytes may infiltrate adipose tissue and contribute to the pathogenesis of inflammation and IR in patients with MetS.…”
Section: Pbmcs From Patients With Mets Are Pre-activatedmentioning
confidence: 83%
“…We have also previously shown that TF antigen on monocytes from PBMCs can be detected by immunofluorescence. 12 Therefore, monocytes are the principle cells capable of TF synthesis. TF plays a significant role in both thrombosis and atherosclerosis.…”
Section: Endotoxin (Lps) Levels In Normal Subjects and Patients With mentioning
confidence: 99%
“…35). Earlier studies implicate CRP in induction of TF expression on blood monocytes (19,36,37), and because of the association of plasma CRP levels with increased risk of cardiovascular events in patients with unstable coronary syndromes, this suggested a prothrombotic role in the pathogenesis of atherosclerosis. Raised plasma levels of SAA are also associated with the pathogenesis of numerous chronic or recurrent inflammatory diseases, including amyloidosis, RA, and atherosclerosis (38,39).…”
Section: Discussionmentioning
confidence: 99%